Innovative Multidisciplinary Approach to Gender Awareness Among University Students: Inovasi Pendekatan Multidisiplin pada Kesadaran Gender Mahasiswa - Suhendra Suhendra; Nadya Kharima; Elvira Winna Permono (Indonesian Journal of Innovation Studies, 2026)
General Background Understanding socially determined differences between men and women requires recognizing both internal and external developmental factors. Specific Background Within higher education institutions, fostering a zero-tolerance environment for inequality necessitates comprehensive gender-responsive policies and student socialization. Knowledge Gap Previous literature has isolated either domestic communication or religious experiences, leaving a theoretical void regarding their simultaneous contribution to equality perception across multidisciplinary perspectives. Aims This quantitative study tests how Family Communication Patterns and spirituality jointly determine the gender awareness of second-year students at UIN Jakarta. Results Multiple regression analysis of 110 respondents reveals that domestic communication and spirituality positively and significantly predict gender awareness, jointly accounting for 20.3% of the variance. Notably, spirituality demonstrated a higher dominant categorization (77.3%) compared to domestic communication frameworks (59.1%). Novelty This research pioneers an integrated model that merges critical-feminist, domestic communication, and spiritual theories to evaluate equality comprehension among youth. Implications University stakeholders and families must collaboratively cultivate balanced domestic dialogues and emphasize profound spiritual meaning over rigid religious dogma to sustainably advance campus equality. Highlights Family communication structures and internal spiritual depth positively predict student gender awareness. Spiritual experiences display a higher dominant categorization than domestic communication in shaping equality perception. Stakeholders must emphasize profound spiritual meaning over rigid religious dogma to advance campus equality. Keywords Family Communication Patterns; Gender Awareness; Spirituality; University Students; Equality Perception